Reading of Jane Austen. - Hardy, Barbara (Continuum International Pub. Group, 2000)
A Reading of Jane Austen (first published by Peter Owen in 1975) has established itself with critics and readers as an outstanding contribution to the growing literature on this author, full of fresh and stimulating perceptions. Central to the word is Barbara Hardy's view of Jane Austen as the originator of the modern novel, largely through her creation of a new and flexible medium enabling her to move easily from sympathy to detachment, from one mind to many minds, from solitary scenes to social gatherings.